ANALYSIS OF TRAINING IN IMPROVING EMPLOYEE PERFORMANCE AT THE GUNUNGSITOLI CITY EDUCATION OFFICE - Sri Salom Harefa; Sukaaro Waruwu; Robin Markus Putra Waruwu; Aferiaman Telaumbanua (LPPM YPITI, 2026)
This study aims to analyze the impact of the implementation of education and training programs (Diklat) on improving employee performance at the Gunungsitoli City Education Office. The focus of the study is directed at the effectiveness of the implementation of the training on employee performance. This study uses qualitative methods, where data is obtained through interviews, observations, and documentation studies with key informants, principal, and supporting staff involved in the training activities.The results of the study indicate that the implementation of training at the Gunungsitoli City Education Office has generally been quite successful and has had a positive impact on improving employee competence, discipline, responsibility, and professionalism. Through training, employees become more skilled and able to adapt to increasingly complex work demands. However, the effectiveness of training implementation has not been optimal due to budget constraints, irregular training implementation, and unequal opportunities for all employees to participate in training. The implications of this study confirm that training plays a strategic role in improving employee performance by strengthening technical competency, discipline, work motivation, and the ability to work collaboratively. Therefore, training must be implemented sustainably, relevant to job needs, and accompanied by post-training evaluation so that its benefits can be effectively implemented in improving the performance of apparatus and professional public services at the Gunungsitoli City Education Office.